2021
DOI: 10.1177/0734242x20982055
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic contamination in a conventional wastewater treatment plant in Thailand

Abstract: Plastic waste has become a global environmental concern. One type of plastic waste is microplastics (MPs), which can spread easily in the environment. Wastewater effluent is one of the land-based sources of MPs. This study investigates the amount of microplastic (MP) pollution in an urban wastewater treatment plant (WWTP) in Thailand. Water samples were collected and examined to find the types, morphology and sources of MPs. Wastewater was filtered through a set of sieves ranging from 5 mm to 0.05 mm. Sludge s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This aspect is of great importance because it is very useful for understanding the origin of particles [81]. From the analysis of the examined literature, among the MPs identified in the SeS, fibers and fragments substantially predominate [35,41,55,[57][58][59]61,[63][64][65][66][67][68][69][70][71][72][73]75,76] (Table 1). Both are already present in the influent WW, the former derive mainly from the washing of synthetic clothing at home or industrial level [82], while the latter are contained for instance in many cosmetics as scrubber, given their irregular shape [3,81,83] or derive from the fragmentation of larger particles [81].…”
Section: From Wastewater To Sewage Sludgementioning
confidence: 99%
“…This aspect is of great importance because it is very useful for understanding the origin of particles [81]. From the analysis of the examined literature, among the MPs identified in the SeS, fibers and fragments substantially predominate [35,41,55,[57][58][59]61,[63][64][65][66][67][68][69][70][71][72][73]75,76] (Table 1). Both are already present in the influent WW, the former derive mainly from the washing of synthetic clothing at home or industrial level [82], while the latter are contained for instance in many cosmetics as scrubber, given their irregular shape [3,81,83] or derive from the fragmentation of larger particles [81].…”
Section: From Wastewater To Sewage Sludgementioning
confidence: 99%
“…The size of most microplastics found in WWTP was different. For example, reference [19] found that the main size was 0.05-0.5 mm whilst reference [7] reported that the major size was 100-355 µm. in WWTP.…”
Section: B Characterization Of Microplasticsmentioning
confidence: 99%
“…Consequently, several plastic particles release into the main river and the Gulf of Thailand. There are only a few studies on the presence of microplastics in the influent and effluent from WWTPs [9], [19], especially from industrial WWTPs which might be a huge source of microplastics contamination in the environment. This work is one of the first studies about the fate of microplastics in central industrial WWTPs in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics are environmental contaminants that have received necessary attention due to their increased quantity and persistence. It is restricted to small plastic pieces ranging from about 5 mm to a few micrometers in diameter (Andrady, 2017;Costa et al, 2018;Accinelli et al, 2019;Yuan et al, 2020;Tadsuwan and Babel, 2021). They are spread within the environment through atmospheric dust, rain, laundry waste, landfill sites, and wastewater treatment plant (Dris et al, 2018;Tadsuwan and Babel, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is restricted to small plastic pieces ranging from about 5 mm to a few micrometers in diameter (Andrady, 2017;Costa et al, 2018;Accinelli et al, 2019;Yuan et al, 2020;Tadsuwan and Babel, 2021). They are spread within the environment through atmospheric dust, rain, laundry waste, landfill sites, and wastewater treatment plant (Dris et al, 2018;Tadsuwan and Babel, 2021). A study showed that 275 million metric tons of plastic waste were generated by 192 countries in 2010.…”
Section: Introductionmentioning
confidence: 99%